2009
DOI: 10.1136/hrt.2008.152017
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric and congenital heart disease in South America: an overview

Abstract: Congenital heart diseases are one of the most common structural defects present at birth, with an approximate incidence of 8 per 1000 live births. As most countries in South America have a high birth rate, they are a significant public health concern. This paper provides a brief overview of the burden of congenital heart disease in South America, focusing on its local prevalence, facilities for treatment and outcomes after medical, surgical or catheter intervention for the most common diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
2
15
0
3
Order By: Relevance
“…Surprisingly, gender equality in the utilisation of healthcare systems has not been evaluated in prospective studies, resulting in varied estimations of gender disparity among similar populations depending on the method used 8 15. Recent reviews of CHD from other developing countries make no mention of gender disparities in healthcare 16. In a retrospective study of paediatric admissions in Hong Kong, a significant gender disparity was found but was suggested to be due to male vulnerability to diseases 17.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, gender equality in the utilisation of healthcare systems has not been evaluated in prospective studies, resulting in varied estimations of gender disparity among similar populations depending on the method used 8 15. Recent reviews of CHD from other developing countries make no mention of gender disparities in healthcare 16. In a retrospective study of paediatric admissions in Hong Kong, a significant gender disparity was found but was suggested to be due to male vulnerability to diseases 17.…”
Section: Discussionmentioning
confidence: 99%
“…This variation is explained by the use of different diagnostic methods that facilitate the detection of less severe heart diseases. Although less frequent, estimates in developing countries are around 8 in 1000 live births [30].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the true incidence or prevalence of congenital heart disease (CHD) for Latin America as a whole has been a true challenge. In South America, the frequency of CHD was estimated to be 9% live births, according to Pedra et al [1]. In Latin America, the reported incidence is variable, according to the Latin American Collaborative Study of Congenital Malformations (ECLAMC).…”
Section: Introductionmentioning
confidence: 99%